International technical conference on plant genetic resources: Preparatory process for Europe - International Plant Genetic Resources Institute; Food and Agriculture Organization of the United Nations; Plant Production and Protection Division (1996)
This publication contains three documents which resulted at the regional level from the preparatory process to the International Technical Conference on Plant Genetic Resources (June 1996 in Leipzig, Germany). The Regional Synthesis on the Status of PGR in Europe which was prepared by IPGRI on the basis of 40 Country Reports submitted to FAO in 1995 served as a working document for the Preparatory Meeting for Europe held in September 1995 in Nitra, Slovakia. The report of this meeting which contains the Region's recommendations for the Global Plan of Action, is the second document in this publication. The Recommendation of the European Forest Genetic Resources Workshop held in November 1995 in Sopron, Hungary deal specifically with the forest genetic resources aspects of the preparatory process. They are included as third document.